Seeking the aim - perspectives of asylum seekers, nurses, and authorities on the objectives of the asylum seekers' initial health assessment: a qualitative study - K-L Mustonen; M. Ismail; T. Mäki-Opas; A.E. Castaneda; J. Kauhanen; S. Atkins; N. Skogberg (BMC, 2024)
Abstract Background A voluntary and free initial health assessment is offered to all asylum seekers upon arrival in Finland. The central aim of this initial health assessment is early identification of service needs. There is, however, limited information on how effective the initial assessment is in fulfilling its aims. This study explores the viewpoints of asylum seekers, reception centre nurses, and health authorities regarding the objectives of the initial health assessment. It serves as a starting point for effectiveness research, where effectiveness is defined as the achievement of intended aims. Methods This qualitative descriptive study is based on 31 semi-structured individual interviews (13 asylum seekers, 14 nurses, and four asylum health authorities) conducted in January and February 2019. Reflective thematic analysis was employed for data analysis, involving initial separate analyses for each group, followed by an assessment of differences and similarities between the groups. Results The importance of a comprehensive initial health assessment and preventing infections was emphasized by all groups. The main differences were views on service needs assessment in relation to persons in vulnerable situation and information provision. All groups described both individual and public health perspectives. Conclusions This study provides valuable insights for developing a more effective assessment. Asylum seekers require comprehensive health assessment and details about their rights. To address these needs, it is crucial to update reception centre nurses' practices. Additionally, authorities responsible for planning and guiding services should refine their instructions concerning the information provided to asylum seekers and persons in vulnerable situations. The findings of this study can be used to enhance information provision and develop targeted training programs for nurses, as well as to evaluate the achievement of established aims.